Immigration and the Dutch disease. A counterfactual analysis of the Norwegian resource boom 2004-2013 - Ådne Cappelen; Torbjørn Eika (Statistics Norway, Research Department, 2017)
The EU-enlargement in 2004 increased labour migration and affected the Norwegian labour market in particular. We study how this modified the Dutch disease effects during the resource boom 2004- 2013. In the Norwegian case the resource movement effect of the petroleum industry has historically dominated the spending effect. One reason is the introduction of the fiscal policy rule in 2001 that limited spending. We find that economic growth in Norway was roughly doubled during this period due to the resource boom while total population increased by 2 percent. Moreover, both the resource movement and spending effects on Mainland GDP were roughly unaffected by immigration while employment increased, real wages fell and so did productivity.
Keywords: B22; J11; Q33; 330; Dutch disease; Immigration